Physicochemical and sensory properties of traditional baked cake (kuih bakar) with coconut milk and soy milk - Idris, Maimanah Faizah; Mohammad Rashedi, Ismail Fitry; M. R., Umi Hartina; Ashari, Rozzamri (Rynnye Lyan Resources, 2020)
Coconut milk is widely used in Malaysia as one of the essential ingredients in preparing traditional baked cake or ‘kuih bakar’. Increased demand for coconut milk affects its availability and cost. Thus, it is important to study a possible alternative ingredient to ensure the continuity of this traditional dessert. This project aimed to determine the physicochemical and sensory properties of ‘kuih bakar’ produced with coconut milk and soy milk. In the present study, ‘kuih bakar’ was prepared with fresh coconut milk (FCM) (positive control), fresh soy milk (FSM), commercial coconut milk (CCM), commercial soy milk (CSM), and without milk (negative control). Proximate analysis showed that substitution of coconut milk with soy milk reduced the fat and increased the protein content of ‘kuih bakar’ significantly (p < 0.05). However, the substitution of coconut milk did not show a significant effect (p > 0.05) on the colour properties and water activity of the sample. There were significant differences (p < 0.05) in scores during sensory evaluation between the samples but the ‘kuih bakar’ produced with FSM showed no significant difference (p < 0.05) as compared to FCM and CCM. This study demonstrated that physicochemical and sensory attributes of traditional ‘kuih bakar’ can be maintained by using FSM as a substitution of the traditional coconut milk used in producing ‘kuih bakar’.